Pengukuran Laju Paparan Radiasi pada Perisai Radiasi Ruang Panoramik di Instalasi Radiologi Rumah Sakit Islam Klaten - Raih Sutejo; Siti Daryati (Poltekkes Kemenkes Semarang, 2016)
Background: Research about the measurement of radiation exposure rate on panoramic radiation shield in Radiology Installation of Klaten Islamic Hospital has been conducted. The background of this research is in the panoramic room there is a veil that has a gap on the bottom as high as 20 cm. The purpose of this research is to know the rate of radiation exposure on radiation panoramic shield in Radiology Installation of Klaten Islamic Hospital and the application of radiation protection system to the room.Methods: This research type is quantitative with survey approach that is writer do observation, documentation and measurement of exposure rate of radiation at controlled and uncontrolled area by doing measurement at two state that is before exposure (background radiation) and after exposure. The data obtained are then analyzed descriptively to declare a safe examination room or not for workers and the general public by comparing the measurement results with UNSCEAR and NCRP report No. 147.Result: The value of the background exposure rate in the panoramic chamber of the Klaten Hospital Radiology Installation exceeds the value of the background dose rate based on the location of the height of an area according to UNSCEAR. The background exposure value in the panoramic space ranges from 0.14 to 0.175 μGy/hour. The actual radiation exposure measurements at point A is 0.00021 mGy/hour, point B is 0.000175 mGy/h, point C is 0 mGy/hour, point D is 0 mGy/hour, point E is 0.000105 mGy/hour, point G is 0,000735 mGy/hour. These six results have not exceeded the NCRP report no. 147 is for controlled areas 0.0025 mGy / hr and uncontrolled area 0.0005 mGy / hr.